Improving the Literacy and Numerical Ability of Students Through the Class 2 Teaching Campus Program - Amalya Husnayain; Hinggil Permana (Peneliti.net, 2022)
Teaching Campus Batch 1I 2021 is part of the Independent Learning Independent Campus (MBKM) program launched by the Ministry of Education and Culture of the Republic of Indonesia (Kemendikbud) and supported by the Education Fund Management Institute (LPDP) of the Ministry of Finance which opens opportunities for students to become educators in Elementary Schools. SD) or Junior High School (SMP) to assist learning during the pandemic, by presenting students as part of strengthening literacy and numeracy learning where students become teachers' partners in creativity and innovation in learning. The Covid-19 pandemic that occurred caused a decrease in student interest in learning, the level of understanding of students when learning, and students' literacy and numeracy abilities. Based on these problems, it affects the effectiveness of the learning process, one of which is at SDN Dawuan Tengah I. The methods used in the Teaching Campus activity number II are in the form of literacy and numeracy habituation activities. The final result of this activity is the habituation of literacy and numeracy for students at SDN Dawuan Tengah I and increasing the real role and contribution of universities and students in national development.